2017
DOI: 10.24815/jdm.v4i2.8863
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Peningkatan Kemampuan Representasi Matematis Siswa SMA Ditinjau dari Perbedaan Gender

Abstract: Mathematical representation is one of the mathematical higher order thinking skills, as a tool or way of thinking in communicating mathematical ideas. Referring to a research about the inconsistency of a mathematical communication profile involving gender differences and the phenomenon of more female students than men right now, there appears to be an allegation that there is a connection between gender differences and students mathematical representation. The purpose of this study is to analyze the improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
2
0
8
Order By: Relevance
“…The problem-solving ability of students of mathematics education study program that was studied previously indicated low ability, especially in geometry problems, where students had difficulty compiling symbolic mathematical models of geometric problems that were presented verbally [3]. The results of this study are in line with Dewi et al [23] that the representation ability of students is low due to the ability to compose a mathematical model (symbolic) and present it in the form of words (verbal). Luo's research [24] also found something similar to this study, namely that a significant percentage of prospective mathematics teachers could not understand the problem of multiplying fractions by being given a symbolic representation.…”
Section: Resultssupporting
confidence: 82%
“…The problem-solving ability of students of mathematics education study program that was studied previously indicated low ability, especially in geometry problems, where students had difficulty compiling symbolic mathematical models of geometric problems that were presented verbally [3]. The results of this study are in line with Dewi et al [23] that the representation ability of students is low due to the ability to compose a mathematical model (symbolic) and present it in the form of words (verbal). Luo's research [24] also found something similar to this study, namely that a significant percentage of prospective mathematics teachers could not understand the problem of multiplying fractions by being given a symbolic representation.…”
Section: Resultssupporting
confidence: 82%
“…Kemampuan repesentasi matematis dapat memfasilitasi siswa untuk mengemukakan ide-ide matematika dari suatu masalah kedalam berbagai macam cara yang telah diketahuinya (Dewi et al, 2017). Ide atau gagasan matematis dapat diungkapkan dalam bentuk gambar atau objek nyata, grafik, diagram, atau simbol-simbol matematika (Ulya & Rahayu, 2020).…”
Section: National Council Of Teacherunclassified
“…Selanjutnya dijelaskan bahwa, multi representasi dapat mendukung konstruksi pemahaman konsep yang lebih mendalam ketika peserta didik menghubungkan representasi tersebut untuk mengidentifikasi fitur dan domain yang digunakan. Representasi digunakan untuk menggambarkan konsep ilmiah (interpretasi); menghasilkan representasi (konstruksi); mengidentifikasi, menjelaskan, dan menganalisis fitur representasi; menghubungkan berbagai representasi dan menjelaskan hubungan di antara mereka (Dewi et al, 2017). Representasi berisi interpretasi dan penjelasan mengenai ide atau konsep ilmiah dengan menggunakan mode seperti analogi, pernyataan verbal, teks tertulis, diagram, grafik, dan simulasi (Eilam & Reiter, 2014).…”
Section: Pembahasanunclassified